Technological Impact and Performance Outcomes: Analyzing Recruitment and Selection in Haryana's IT Sector (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study investigates the influence of digital tools and technology on the recruitment and selection processes within the IT industry in the National Capital Region (NCR) of Haryana, India, and their impact on organizational performance and growth. The research objectives aim to explore the adoption and effectiveness of technological advancements in recruitment practices and to measure their direct effects on the performance metrics of IT companies in the region. Employing an empirical approach, data was gathered through an online survey with a sample of 150 IT professionals using random sampling methods. The findings emphasize the critical role of technological integration in enhancing recruitment outcomes and, by extension, improving organizational performance in the IT sector. This study contributes to both academic literature and industry practices by demonstrating how digital advancements can optimize hiring processes and drive business growth, making a compelling case for continued technological investment in human resources strategies.